RETRACTED: Shi et al. Surface Hydrophilic Modification for Chip of Centrifugal Microfluidic Immunoassay System. Micromachines 2022, 13, 831 - Yuxing Shi; Peng Ye; Chuang Wang; Kuojun Yang; Jinhong Guo (Micromachines)
The journal retracts the article titled “Surface Hydrophilic Modification for Chip of Centrifugal Microfluidic Immunoassay System” [...]